Portable human HBV DNA detection and quantification using invertase-based system / Eddy Hasrul Hassan - Hassan, Eddy Hasrul (Research Innovation Business Unit, 2014)
Hepatitis B virus (HBV) DNA detection and quantification has important roles in early disease discovery, disease progression monitoring, treatment, and management in the long-run. Many well developed methods and techniques used routinely in medical centres and research laboratories for the detection of the DNA are time-consuming and costly from samples preparation to result delivery. Glucose meters can quantitatively detect target molecules in a solution, a necessity for diagnosis and detection, but only responds to one chemical: glucose. A novel approach by coupling it with a class of molecular sensors called functional DNA sensors will enable detection of the targets. Objectives: This study will utilise the action of invertase enzyme to transform DNA into glucose in developing a cost-effective, portable, and rapid HBV DNA quantification device for public or on-site use. The results of this study could revolutionise and facilitate medical diagnosis and management of infectious diseases particularly hepatitis B with highly cost-effective and simpler solution. Methodology: The quantification is based on target dependent binding of cDNA-invertase conjugate with the analyte DNA, thereby transforming the concentration of DNA in sample into glucose through invertase-catalysed hydrolysis of sucrose for the readout in a glucose meter. Outcomes: This study would provide novel alternative method for HBV DNA quantification on-site without the high costs and long waiting period of sending samples to professional laboratories. Moreover, portable and cost effective methods that are directly usable by the public can facilitate early detections to reduce the hazard of the diseases and are also affordable for low income countries and regions.